The Relationship Between Low Socioeconomic and Depressive Symptoms: A Case Report - Ridlo, Fairuz; Rasyid, Rezza Dwi Ar; Karida, Rika Nur; Prisnidiawati, Ajeng; Basuki, Shinta Maulydiyah; Kasiani, Tutik Nur; Algristian, Hafid (Medicor : Journal of Health Informatics and Health Policy, 2025)
Depression is a prevalent mental health disorder that significantly impacts both individual well-being and broader societal functioning. Socioeconomic disadvantage manifested through low income, limited educational attainment, and reduced access to mental health care has consistently emerged as a key risk factor for the development and persistence of depressive symptoms. In Indonesia, the mental health burden among low income populations remains under recognized and under treated. This case report details the clinical presentation of a 35-year-old woman diagnosed with major depressive disorder, originating from a low socioeconomic background. The patient experienced chronic psychological distress linked to financial instability, family rejection, and social stigma related to her informal digital employment. Data were collected through comprehensive psychiatric evaluation, including structured interviews, mental status examination, and physical assessment, in accordance with DSM-5 diagnostic criteria. The patient's symptoms marked by insomnia, anhedonia, anxiety, suicidal ideation, and psychosomatic complaints highlight the complex interplay between environmental hardship and mental health. Her case exemplifies how economic precarity and insufficient social support contribute to both emotional and physical deterioration. This report not only contributes to a deeper understanding of depression among socioeconomically marginalized individuals in Indonesia but also emphasizes the importance of culturally contextualized mental health strategies. It advocates for community based, low barrier interventions that incorporate psychosocial and economic dimensions. Ultimately, addressing mental health within low SES populations requires holistic approaches that extend beyond clinical treatment and include policy reforms focused on employment protection, social welfare, and anti-stigma efforts.